Envolvimento de marcadores do metabolismo mineral ósseo com parâmetros de hemólise, função renal e inflamação em pacientes com anemia falciforme - Abreu, Gabriela Araujo de (2023)
Sickle cell anemia (SCA) is characterized by vaso-occlusive crises, hemolysis, chronic inflammation, and complications such as nephropathy, which has as consequences increase of tubular reabsorption of phosphate and reduction of vitamin D activation. There is high energy expenditure and inadequate absorption of nutrients, leading to nutritional deficiencies, such as hypovitaminosis D. These factors can lead to changes in bone mineral metabolism and, consequently, to the worsening of the disease. The aim of this study was to evaluate the relationship between markers of bone mineral metabolism and hemolysis, inflammation and renal function parameters in SCA patients. This is a cross-sectional and analytical study including 88 patients with SCA on outpatient follow-up and 31 blood donors. Sociodemographic, clinical and laboratory data were obtained from clinical records and interviews. Parathyroid hormone (iPTH) and 25-hydroxyvitamin D (25(OH)D) were measured by electrochemiluminescence and fluorimetric method, respectively. Serum and urinary creatinine, serum and urinary proteinuria, calcium and phosphate, and serum albumin were obtained by colorimetric method and C-reactive protein and albuminuria by immunoturbidimetry. A p-value < 0,05 was adopted. Compared to controls, patients with SCA had a significant reduction in serum calcium (8.27 x 10.42 mg/dL), calciuria (57 x 124 mg/g-Cr), and 25(OH)D (25 x 30 ng/mL). There was also an increase in serum phosphate (3.86 x 3.46 mg/dL) and maximal tubular reabsorption of phosphate (MTRP) (3.6 x 3.21 mg/dL), with no change in iPTH, tubular reabsorption of phosphate (TRP) and phosphaturia. Serum phosphate was correlated with TRP (ρ = 0.32) and with MTRP (ρ = 0.9). In comparison to control group, the use of HU and HbF ≥ 10% were associated with a reduction in serum phosphate (3.95 x 3.6 x 3.4 mg/dL and 4.1 x 3.6 x 3.4 mg/dL, respectively), TRP (98.04 x 96.14 x 95.28% and 97.66 x 96.14 x 95.28%, respectively) and MTRP (5.21 x 4.43 x 4.2 mg/dL and 5.23 x 4.3 x 4.2 mg/dL, respectively). Assessing the occurrence of painful crises, MTRP was increased (4.63 x 4.42 x 4.2 mg/dL), which was not reflected in the frequency of crises. Those with moderate/severe anemia presented increased serum phosphate (4.0 x 3.6 x 3.4 mg/dL) and MTRP (4.98 x 4.42 x 4.2 mg/dL). Thus, serum phosphate, TRP and MTRP may be good candidates for markers of severity in SCA.